المدن الإسلامية في المغرب - Gaetano Palumbo (13911798) (2023)
This item is an Illustrated Presentation produced by UCL Qatar as part of the The Transformation of the Moroccan Landscape During the Early Islamic Period Project, and is part of Islamic Cities in Morocco School Pack - Arabic collection.  The Illustrated Presentation  is for 12 - 16 years age groups. This work was illustrated by Charlene Kasdorf.